Case Report: Negative pressure wound therapy with instillation and dwell time as adjuvant therapy for limb salvage in a complicated necrotizing fasciitis on ischemic diabetic foot - Chen, Shiuan-Fu; Chang, Chang-Cheng (Frontiers in Surgery, 2026)
BackgroundNecrotizing fasciitis superimposed on ischemic diabetic foot ulcers represents a complex and limb-threatening condition, especially in patients with multiple comorbidities such as end-stage renal disease, peripheral arterial occlusive disease, and poorly controlled diabetes mellitus. Optimal wound management strategies that minimize surgical burden while enhancing infection control and tissue regeneration are essential. This case highlights the use of multimodal adjuvant therapies and multidisciplinary management for limb salvage in a high-risk patient.Case presentationA 60-year-old woman with a Wagner grade 4 ischemic diabetic foot ulcer complicated by deep invasive necrotizing fasciitis underwent urgent extensive debridement, fasciotomy, and sequestrectomy, resulting in a large soft tissue defect with substantial bone and tendon exposure.ManagementA staged wound management approach was adopted, beginning with negative pressure wound therapy with instillation and dwell time using normal saline to promote bioburden reduction and granulation tissue formation. This was followed by the application of a dermal substitute combined with conventional negative pressure wound therapy to support dermal regeneration. Throughout the treatment course, multidisciplinary care was provided to optimize the management of systemic comorbidities.OutcomeAfter four cycles of negative pressure wound therapy with instillation and dwell time, more than 70 percent of the wound bed, including previously exposed bone and tendon areas, was covered with healthy granulation tissue. Over the following three months, further tissue regeneration was achieved with the dermal substitute and negative pressure wound therapy. No additional surgical debridement was required, and limb preservation was successfully maintained without progression to systemic sepsis. Functionally, the patient ambulated with mobility assistance and reported minimal pain with good treatment acceptability. The patient subsequently died at month 5 from cardiovascular disease unrelated to the wound; wound stability through month 5 was recorded only in treating-team documentation.ConclusionThis case demonstrates that a carefully staged multimodal adjuvant therapy protocol, incorporating negative pressure wound therapy with instillation and dwell time, dermal substitute application with negative pressure wound therapy, and multidisciplinary management of comorbidities, can serve as an effective limb salvage strategy in high-risk patients with diabetic foot ulcer-associated necrotizing fasciitis and extensive soft tissue defects when conventional reconstructive options are not feasible. This multimodal protocol may inform practice in high-risk or resource-limited settings.